An Investigation into Five Methods of Student Reflection - Chapple, Katherine (STER, 2019)
Being the centre of the learning poses challenges for students and teachers and it is these challenges that this research seeks to investigate. Investigating the benefits and drawbacks of methods of reflection, five methods are chosen that the researcher has previously used and which secondary school teachers are encouraged to use by the Department of Education, in the new Junior Cycle course (DES 2015). This study seeks to assess student’s reflection from both the student’s and the teacher’s perspective and how reflection could be guided and promoted by the teacher. At its core, the research posed the question to students “Is reflection an effective way to learn?”. This research recorded both academic and non-academic benefits and negatives of student reflection in theory and in literature both in an Irish and an international context.
Journal Article
Keywords: Research Subject Categories::SOCIAL SCIENCES; Reflection; Junior Cycle; Post-Primary Education; Assessment; STER